Türkiye’de Kafkasya tarihi araştırmaları (1923-1991) - Genç, Hülya (My University, 2025)
Türkiye’nin komşusu konumunda bulunan Kafkasya, tarih boyunca stratejik konumu sebebiyle önemli bölgelerden biri olmuştur. Bununla birlikte Kafkasya’da Türk-İslam kültürünün hâkim unsur olması Kafkasya’yı Türkiye için daha da önemli hale getirmektedir. Bu ilişkilerin yansıması olarak, Türkiye’de Kafkasya tarihine yönelik kapsamlı bir literatür oluşmuştur; bu literatür de hem telif ve hem de tercüme kitaplar bulunmaktadır. Türkiye Cumhuriyeti’nin kuruluşundan İkinci Dünya Savaşı’nın sonuna kadarki süreçte kitaplar sayı bakımından az olmakla birlikte, Türkiye’de Kafkasya tarihi üzerine yapılan çalışmaların temelini oluşturmaktadır. Soğuk Savaş döneminin en sert yaşandığı yıllarda Kafkasya tarihi ile ilgili yayımlanan eserlerin sayısında hem artış hem de içeriğinde değişim gözlenmektedir. Helsinki Nihai Senedi’nin imzalanması uluslararası diyalog sürecinin başlaması ile birlikte Kafkasya tarihine dair yayımlanan sayısında önemli bir artış gerçekleşmiştir. Kafkasya’nın bir bütün olarak değerlendirilmediği, farklı etnik köken, dil ve din milletlerin olduğu yavaş yavaş anlaşılmaya başlanması bu alanda kitapların sayısının artışını doğrudan etkiledi. Bu çerçevede, Türkiye’de Kafkasya tarihi üzerine yapılan çalışmalarda, iç ve dış gelişmelerin yayımlanan kitapları nasıl şekillendirdiği ortaya konulmaya çalışılmıştır. Yayımlanan kitaplar analiz edilerek Türkiye’de Kafkasya tarihçiliğinin gelişim süreci incelenmiştir.

The Caucasus, which shares a border with Turkey, has hictorically been one of the most significant regions due to it stategic location. Moreover, the dominance of Turkic-Islamic culture in the Caucasus makes the region even more important for Turkey. In this context, both original and translated books on the history of the Caucasus have been published in Turkey. Although the number of such publications between the foundation of Republic of Turkey and the of Word War II was limited, these works laid the foundation for Caucasian historical studies in the country. During the height of the Cold War, there was not only an increase in the number of works published on the number of works published on the history of the Caucasus, but alsa a change in their content. Following the signing of the Helsinki Final Act and the initiation of international dialogue, many new books on the history of the Caucasus were published. As the perception of the Caucasus evolved from being viewed as amonolithic entity to a diverse region with various ethnicities, languages, and religions, the number of publications in the field increased. In line with this development, our study takes this transformation into account. In the second and third chapters, books are analyzed according to political and georraphical subdivisions. The stud also explores how domestic and international developments in Turkey influenced the nature and content of these publications. Through the analysis of the books published on the Caucasus, the evolution of Caucasian historiography in Turkey is examined.
Keywords: Armenia; Azerbaijan; Azerbaycan; Caucasus; Çeviri Eserler; Ermenistan; Georgia; Gürcistan; History; Kafkasya; Orginal Works; Tarih; Telif Eserler; Translated Works